Periodic fluorescence variations of CdSe quantum dots coupled to aryleneethynylenes with aggregation-induced emission - Kumar, Krishan; Hiller, Jonas; Bender, Markus; Nosrati, Saeed; Liu, Quan; Edelmann, Marc; Maier, Steffen; Rammler, Tim; Wackenhut, Frank; Meixner, Alfred J.; Braun, Kai; Bunz, Uwe H. F.; et al. (ACS nano, 2021)
CdSe nanocrystals and aggregates of an aryleneethynylene derivative are assembled into a hybrid thin film with dual fluorescence from both fluorophores. Under continuous excitation, the nanocrystals and the molecules exhibit anticorrelated fluorescence intensity variations, which become periodic at low temperature. We attribute this to a structure-dependent aggregation-induced emission of the aryleneethynylene derivative, which impacts the rate of excitation energy transfer between the molecules and nanocrystals. This work highlights that combining semiconductor nanocrystals with molecular aggregates, which exhibit aggregation-induced emission, can result in emerging optical properties.
Gesehen am 22.07.2021